PENINGKATAN KEMAMPUAN BERCERITA DENGAN MENGGUNAKAN MEDIA GAMBAR BAGI SISWA KELAS VII A SMP BHAYANGKARI KARANGPANDAN KABUPATEN KARANGANYAR SEMESTER GASAL TAHUN PELAJARAN 2009/2010 - Sukidi Sukidi (Jurusan Tadris Bahasa Indonesia, 2016)
Classroom action research was conducted with the aim of: 1. To enhance the learning process for students tell the class VII A junior Bhayangkari Karangpandan, 2. To improve the ability to tell the students of class VII A junior Bhayangkari Karangpandan. Execution carried out in two cycles, each cycle consisting of four (4) steps of activities, namely planning, action, observation and reflection. Prior to the first cycle begins with the initial research activities to find out the condition of the subjects. Based on preliminary research results compiled in the form of research, planning learning implementation plan. First cycle of action as an effort to improve the conditions stated lack of or low on the initial research. Activity Cycle II, the efforts to repair/ improvement of a state which is still less in the first cycle. The result of study shows that low-ability students to tell based on initial research, one of which caused no/ not use the GCC appropriate learning media to achieve the expected competencies. In this study, the actions taken to improve the process and learning outcomes using instructional media telling picture. After doing the action over the past two cycles, the results showed that by using media images as well the ability to tell the students can be improved.Â